2020
DOI: 10.21203/rs.3.rs-56283/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Study on the levels of calcitonin gene-related peptide, somatostatin and inflammatory factors in patients with coronary artery  disease complicated with type 2 diabetes mellitus

Abstract: BackgroundTo evaluate the level and correlation of serum neuropeptide cakiNnin gene-elated peptide (CORP), somatostatin (SS) and inflammatory factors (CRP, TNF-o, MCP-1 and sICAM-1) in patients with coronary atherosclerotic heart disease (CAD) complicated with type 2 diabetes mellitus (DM), to explore the mechanism of diabetic patients prone to complicated CAD.MethodsPatients were divided into three groups according to corcmary angiography results and whether there was a history of type 2 diabetes: control gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
0
1
0
Order By: Relevance
“…According to relevant research, the patients with early diabetes are characterized by damp heat, marked weakness, weakness of glucose tolerance, treatment of dampness and spleen, clearing away heat and dampness. [17,18] According to relevant studies [19] , the effect of Simiao particles on early type 2 diabetic patients is significant, which can effectively reduce the levels of FBG and PBG, FINS and HbAlc. HOMA-IR, IAI, BMI and other indicators of the patient were significantly improved, without adverse reactions.…”
Section: Drying Dampness and Strengthening Spleenmentioning
confidence: 99%
“…According to relevant research, the patients with early diabetes are characterized by damp heat, marked weakness, weakness of glucose tolerance, treatment of dampness and spleen, clearing away heat and dampness. [17,18] According to relevant studies [19] , the effect of Simiao particles on early type 2 diabetic patients is significant, which can effectively reduce the levels of FBG and PBG, FINS and HbAlc. HOMA-IR, IAI, BMI and other indicators of the patient were significantly improved, without adverse reactions.…”
Section: Drying Dampness and Strengthening Spleenmentioning
confidence: 99%
“…According to the theory of traditional Chinese medicine (TCM), acupuncture can regulate qi and blood and have a direct impact on bioavailability of substances of the body [18]. In the past 20 years, several randomized controlled trials (RCTs) have been conducted on the effectiveness of acupuncture on diabetes mellitus and its complications [19][20][21]. It has been demonstrated that acupuncture may improve insulin sensitivity [18,22] and c-peptide levels through effective treatment against metabolic disturbances such as hyperglycaemia [21,23,24], overweight [24,25], inflammation [26], while improving lipid metabolism [27].…”
Section: Introductionmentioning
confidence: 99%
“…According to the theory of traditional Chinese medicine (TCM), acupuncture can regulate qi and blood and have a direct impact on bioavailability of substances of the body [18]. In the past 20 years, several randomized controlled trials (RCTs) have been conducted on the effectiveness of acupuncture on DM and its complications [19][20][21]. It has been demonstrated that acupuncture may improve insulin sensitivity [18,22] and c-peptide levels through effective treatment against metabolic disturbances such as hyperglycemia [21,23,24], overweight [24,25], in ammation [26], while improving lipid metabolism [27].…”
mentioning
confidence: 99%